Eco-friendly database space saving using proxy attributes - Emran, Nurul Akmar; Abdullah, Noraswaliza; Harum, Norhayati; Ismail, Amelia Ritahani; Nordin, Azlin; Caballero, Ismail (Facultad de Informatica, Universidad Nacional de La Plata, 2022)
Rapid data growth and inefficient data storage are two concerning issues that are becoming more and more important in green computing. The decision on the eco-friendly technology to use often relies on the amount of carbon footprint produced. Thus, it would be valuable to avoid inefficient electric power utilization by minimizing physical data storages to store large data volumes. This paper reported the implementation of proxy attributes to reduce space by optimizing the available database space through attributes substitution. We examine a set of proxies retrieved from the public databases regarding their space-saving and accuracy properties. The results indicated that useful proxies that can offer space- saving while maintaining accuracy are available. The findings contribute in understanding the practicality of proxies and their potential in database space-saving.